Gradual rewarming with a hemoglobin-based oxygen carrier improves viability of donation after circulatory death in rat livers - Mahboub, Paria; Aburawi, Mohamed; Ozgur, O. Sila; Pendexter, Casie; Cronin, Stephanie; Lin, Florence Min; Jain, Rohil; Karabacak, Murat N.; Karimian, Negin; Tessier, Shannon N.; Markmann, James F.; Yeh, Heidi; et al. (Frontiers in Transplantation, 2024)
Background Donation after circulatory death (DCD) grafts are vital for increasing available donor organs. Gradual rewarming during machine perfusion has proven effective in mitigating reperfusion injury and enhancing graft quality. Limited data exist on artificial oxygen carriers as an effective solution to meet the increasing metabolic demand with temperature changes. The aim of the present study was to assess the efficacy and safety of utilizing a hemoglobin-based oxygen carrier (HBOC) during the gradual rewarming of DCD rat livers. Methods Liver grafts were procured after 30 min of warm ischemia. The effect of 90 min of oxygenated rewarming perfusion from ice cold temperatures (4 °C) to 37 °C with HBOC after cold storage was evaluated and the results were compared with cold storage alone. Reperfusion at 37 °C was performed to assess the post-preservation recovery. Results Gradual rewarming with HBOC significantly enhanced recovery, demonstrated by markedly lower lactate levels and reduced vascular resistance compared to cold-stored liver grafts. Increased bile production in the HBOC group was noted, indicating improved liver function and bile synthesis capacity. Histological examination showed reduced cellular damage and better tissue preservation in the HBOC-treated livers compared to those subjected to cold storage alone. Conclusion This study suggests the safety of using HBOC during rewarming perfusion of rat livers as no harmful effect was detected. Furthermore, the viability assessment indicated improvement in graft function.